Implementasi Identitas Kependudukan Digital di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidenreng Rappang: Analisis Faktor Pendukung dan Penghambat - Ahmadi, Rezky; Erfina, Erfina; Asad, Muhammad Arisal; Sapri, Sapri; Dema, Herman (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to analyze the implementation of Digital Population Identity (IKD) at the Population and Civil Registration Office of Sidenreng Rappang Regency and identify the supporting and inhibiting factors using Edward III's policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The approach used was descriptive qualitative with data collection techniques through observation, semi-structured interviews, and documentation. The data obtained were analyzed using the Miles and Huberman method with the help of NVivo 12 Plus software. The results show that the implementation of IKD has not been optimal, with an adoption rate of only 2.08% of the total population who have e-KTP. Supporting factors include adequate human resource competencies and the availability of basic technological infrastructure. In contrast, inhibiting factors include low public awareness, uneven socialization, limited internet network, and activation procedures that still require direct presence at the Disdukcapil office. This research is novel in examining the implementation of IKD in areas with limited infrastructure and low digital literacy, which has not been widely discussed in previous studies. Practically, the results of this study can serve as a reference for local governments in developing strategies to optimize IKD implementation, especially in expanding the reach of socialization and improving digital infrastructure. From a theoretical perspective, the findings strengthen Edward III's policy implementation model by highlighting the complex interactions between communication, resources, disposition, and bureaucratic structure in the context of digital policy.